Colorful Underwater World - Srifa, Kittithat (Siam Communication Review, 2022)
“Photographs don't save the world. But the photograph serves to record the beauty of the world. It makes us see how livable the world is.” Photography is the work of a photographer. That serves to record the story or events in which the photographs themselves. There are many different classifications. One of them is underwater photo which this type of image has a lot of memory Therefore, there are few photographers of this type. Which underwater photography will make us see "Colorful underwater world", which this academic article aims to describe the characteristics of general underwater photography, basic underwater photography equipment and limitations of underwater photography the scope of this article is only an introduction to beginners in underwater photography. Because underwater photography is risky those interested in underwater photography should only be learned properly according to the curriculum which will lead to "Aesthetics under the sea"